Carmen A. Serrano, Gothic Imagination in Latin American Fiction and Film, University of New Mexico Press, Albuquerque, 2019. ISBN 9780826360441. - Inés Ordiz (Universitat Autònoma de Barcelona, 2020)
Carmen A. Serrano, Gothic Imagination in Latin American Fiction and Film, University of New Mexico Press, Albuquerque, 2019. ISBN 9780826360441.